Perlakuan Terhadap Narapidana Militer Yang Memiliki Penyakit Menular HIV/AIDS - Arief Fahmi Lubis (Universitas 17 Agustus 1945 Semarang, Indonesia, 2019)
Military convicts are not only objects but also subjects who are no different from other humans who can at any time make mistakes or mistakes that can be punished, so they do not have to be eradicated. The aim of this research is to emphasize that military prisoners are inmates with the status of TNI Soldiers, and must be treated well and humanely in an integrated training system. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description at the time of the research. The results of this research show that the treatment of inmates based on the prison system is not in accordance with the correctional system based on Pancasila and the 1945 Constitution which is the final part of the punishment system. The correctional system is a series of law enforcement that aims to ensure that inmates realize their mistakes, improve themselves, and not repeat criminal acts so that they are ready to rejoin their unit to carry out their duties and responsibilities in the unit, and can live a normal life as soldiers with the spirit of the Sapta Marga and implement the 8 TNI Obligations.